Traces of Time and Chinese Culture: an Analysis of the Historical Tourism Opportunities of Semarang's Ancient Temple - Ufi Saraswati; Alexander Raymon (Universitas Hamzanwadi, 2026)
This study aims to identify the architectural characteristics, spatial organization, and ornamental features of four ancient Chinese temples located in the Old Chinatown area of Semarang, and to analyze their symbolic meanings as a basis for formulating the potential of these temples as an area-based historical tourism narrative. The research adopts a qualitative cultural-arts approach through field observation, semi-structured interviews, and literature review focusing on architecture, ornaments, symbols, and the social functions of the temples, supported by descriptive–comparative analysis and data triangulation. The results show that all four temples share a simple spatial configuration consisting of a front veranda and a main worship hall, a predominance of wooden construction, and a rich repertoire of ornaments featuring mythological fauna, flora, and cosmological symbols, with red and gold as dominant colors representing prosperity and balance. The findings confirm that the temples function not only as places of worship but also as living heritage that embodies history, identity, and the collective memory of the Chinese community in the Old Chinatown area. The implications of this study indicate that these ancient temples have strong potential to be developed as area-based heritage religious tourism assets, provided that their sacred values, symbolic meanings, and the central role of the local community in management and interpretation are consistently maintained.